Serum Glucose-Phosphate Ratio on Admission as a Potential Biomarker for Severity, Functional Outcome, and Recurrence in Acute Ischemic Stroke - Li J; Ma W; Tang W; Yang K; Gu H; Shi J; Chen F; Xu C; Gu S; Wang Y (International Journal of General Medicine)
Jie Li,1,* Wenyang Ma,1,* Wuzhuang Tang,1 Kaixuan Yang,2 Hongqiu Gu,2 Junfeng Shi,1 Feng Chen,1 Chenhan Xu,1 Shiyuan Gu,1 Yongjun Wang2,3 1Department of Neurology, The Affiliated Yixing Hospital of Jiangsu University, Yixing, People’s Republic of China; 2China National Clinical Research Center for Neurological Diseases, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China; 3Department of Neurology, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shiyuan Gu; Yongjun Wang, Email shiyuan1178@hotmail.com; yongjunwang@ncrcnd.org.cnBackground and Objective: Raised serum glucose-phosphate ratio on admission is associated with severity and poor outcome of aneurysmal subarachnoid hemorrhage and severe traumatic brain injury. However, its role in acute ischemic stroke (AIS) remains still unknown. Therefore, this prospective study aimed to investigate the association between admission serum glucose-phosphate ratio and the severity and 1-year clinical outcome of AIS.Methods: All the patients with AIS were enrolled from the Third China National Stroke Registry III. Participants were classified into four groups according to quartiles of admission serum glucose-phosphate ratio levels. Multiple regression models and restricted cubic splines were performed to evaluate the association between serum glucose-phosphate ratio and the severity and 1-year outcome of patients with AIS.Results: Among the 5,541 participants, the mean age was 62.3 years, and 69.4% patients were men. As the quartiles of admission serum glucose-phosphate ratio increased, the median NIHSS score raised, the percentage of moderate and severe stroke elevated, and rates of poor functional outcomes and recurrent stroke raised at one-year follow-up. After adjusting conventional risk factors, the highest admission serum glucose-phosphate ratio-level quartile group showed an association of poor functional outcome and stroke recurrence [OR (95% CI): 1.67 (1.28, 2.17) and HR (95% CI): 1.44 (1.08, 1.92), respectively], relative to the lowest group. Restricted cubic splines showed no significant nonlinear relationship between serum glucose-phosphate ratio and adverse outcomes of AIS.Conclusion: Admission serum glucose-phosphate ratio may be a potential blood biomarker for reflecting stroke severity, predicting poor functional outcomes, and stroke recurrence.Keywords: serum glucose-phosphate ratio, acute ischemic stroke, outcome, severity, blood biomarker